Strategi Pembelajaran Talempong Pacik bagi Siswa Disabilitas Intelektual di SLB Negeri 1 Padang - Cecep Permana; Zaharul Lailiddin Bin Saidon; Sajastanah Bin Imam Koning (Grenek: Jurnal Seni Musik, 2026)
This study aims to describe the implementation of traditional music learning, talempong pacik, for students with intellectual disabilities at SLB Negeri 1 Padang. The focus of the study includes learning strategies, obstacles, and the resulting impacts. The study used a descriptive qualitative approach. Data were collected through semi-structured interviews with music teachers as key informants, as well as observation and documentation for triangulation. Data analysis refers to the Miles and Huberman model, namely data reduction, data presentation, and conclusion drawing. The results show that talempong pacik learning is implemented adaptively according to students' cognitive and motor abilities. The strategies used include exposure, practice, individual approaches, visual cues, and direct practice. The main obstacles include limited concentration, low memory, and limited learning media. This learning has a positive impact on students' motor coordination, concentration, self-confidence, and social interaction. Talempong pacik has the potential to be a medium for cognitive, affective, and psychomotor development.